An observational study of direct oral anticoagulant awareness indicating inadequate recognition with potential for patient harm. (21st March 2016) - Olaiya, A.; Lurie, B.; Watt, B.; McDonald, L.; Greaves, M.; Watson, H. G.
Abstract : Essentials Ignorance of direct oral anticoagulants' effects on coagulation tests may be a safety issue. An electronic questionnaire was sent to prescribers in NHS Grampian with 143 respondents. We found widespread evidence of inappropriate interpretation of the clinical scenarios given. The study suggests potential for patient harm due to lack of knowledge and education is required. Summary: Background: Lack of awareness of the nature of the direct oral anticoagulants (DOACs) combined with the poor correlation between routine coagulation test prolongation and the activity of these drugs represents a potential for patient harm. Objectives: To establish the level of awareness of the different DOACs, and to assess whether prescribers were able to recognize the state of anticoagulation in a hypothetical patient. Methods and results: An electronic questionnaire was sent by email to prescribers in our health board. Among 143 respondents, we found significant differences in awareness of the currently licensed drugs. Of the respondents, 88%, 80% and 50%, respectively, recognized rivaroxaban, dabigatran, and apixaban. When provided with a routine clinical situation, only 13.5%, 17.5% and 16.8%, respectively, recognized that the hypothetical patient was anticoagulated, and only 55–58% recognized that it was unsafe to proceed with an invasive procedure. Conclusion: These results indicate a significant risk for patient harm related to lack of knowledge about this new group of frequently used drugs, and indicate that additional education and training on this subject are required.